Impact of a checklist used by pharmacists on hospital antimicrobial use: a patient-level interrupted time series study. Issue 3 (November 2019) - Fortier, M.; Pistre, P.; Ferreira, V.; Pinsonneault, M.; Charbonneau, J.M.; Proulx, C.; Buisson, A.; Morency-Potvin, P.; Williamson, D.; Ang, A.
Summary: Background: Antimicrobial misuse leading to drug resistance is a growing concern for clinicians. Improving antimicrobial stewardship programmes through development of new tools could be part of the solution. Aim: To evaluate antimicrobial use in hospitalized patients after implementation of an antimicrobial checklist for ward-based clinical pharmacists. Methods: A checklist based on quality indicators of optimal antimicrobial use was implemented to standardize hospital pharmacists' assessments of antimicrobial therapy. Antimicrobial use metrics from adults hospitalized during the control and intervention periods were assessed in an interrupted time series analysis of individual patient data. The primary endpoint was days of therapy (DOT) for all antimicrobials per 1000 days present for included patients. Secondary endpoints were the DOT of extended-spectrum antimicrobials (DOT-ES), length of therapy of all antimicrobials (LOT) and the number of pharmacist interventions. Findings: One-thousand six-hundred and nineteen patients were included: 800 and 819 in the pre- and post-checklist implementation periods, respectively. As indicated by the point estimates and their 95% confidence intervals (CIs), there were no changes in trend for DOT, DOT-ES or LOT. A change in level was not found for the DOT, while a change of -118 DOT-ES [-209, -28] and -51 LOT [-97, -4] was documented. Furthermore, pharmacists' interventions regarding antimicrobials increased by 18.7% (14.0, 23.5) and progress notes by 32.3% (27.8, 36.8). Conclusion: An antimicrobial checklist used by ward-based clinical pharmacists did not decrease DOT for all antimicrobials, but decreased DOT-ES and LOT upon its implementation.